A Discourse Analysis: Cohesion of the Introduction Section of Research Article - Anis Firdatul Rochma; Sulis Triyono (Journal of English Language Teaching and Linguistics, 2019)
As an effort to give contribution to the existing knowledge, it is expected for the undergraduate students to compose an engaging research article in order to convince the readers about the importance of the research article. However, there is only a little attention given to the articles written by the undergraduate students although it is considered very critical to examine whether the exposure of English academic writing has significantly enhances the writing competence of the students. Furthermore, as it is also very crucial to build a meaningful semantic meaning among the sentences in order to disclose the worthiness of the research article, it is essential to analyze the cohesion of the research article written by the undergraduate students. Henceforth, the present research is projected to investigate the cohesion of the research articles written by the undergraduate students of English Language Teaching. As the introduction section of research article is likely to be an area to portray the logical explanation of the research, the present research solely focuses on examining the cohesion of the introduction section of research article. By adopting a qualitative design and involving several steps to analyze the introduction section, it is revealed that the grammatical cohesion is considered to be the most utilized type of cohesion in writing the introduction section. Still, the lexical cohesion is also necessary to build an eloquent semantic meaning about the topic as well the importance of the research article.